Factors affect the Malaysian secondary bond market liquidity - Yong, Hua Yeo (2023)
This paper is intended to investigate the factors that have a significant impact on bond market liquidity in Malaysia. This study develops both internal bond characteristics and overall macroeconomics factors that may affect bond liquidity. According to research, Malaysia's bond market is underdeveloped in comparison to the equity market, despite the fact that in other countries, bonds serve as a relatively cheap source of capital for the borrower and a fixed income earning investment for the investor. However, this will only be possible if the bond market provides sufficient liquidity to the investor.